Kegiatan Pendampingan Pengelolaan Perpustakaan Sekolah sebagai Upaya Penguatan Kapasitas Staf di Kecamatan Ngajum Kabupaten Malang - Rifqi, Ach. Nizam; Puspitadewi, Ganis Chandra; Fajriyah, Annisa (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This community service program aimed to enhance the capacity of school library staff in Ngajum District, Malang Regency. The approach employed Participatory Action Research (PAR) through a workshop model consisting of interactive lectures, group discussions, hands-on practice, and follow-up monitoring. The workshop covered three main aspects: institutional and infrastructural foundations, library services and human resources, and collection management with the use of information technology through the Integrated Library System (SLiMS). A total of 32 participants, mostly teachers assigned as part-time library managers, joined the program. Evaluation results indicated a high level of participant satisfaction, with a grand mean score above 3.5, where the staff service indicator achieved the highest rating. The program proved effective in strengthening participants’ understanding, practical skills in library management, and readiness to utilize technology to support the school library’s role as a modern and sustainable learning resource center.